US Defense Politics the origins of security policy - Sapolsky, Harvey M. 1939-; Gholz, Eugene 1971-; Talmadge, Caitlin (Routledge, 2021)
This book provides an accessible overview of US defense politics for upper-level students. This new edition has been updated and revised, with new material on the Trump Administration and Space Force.Analyzing the ways in which the United States prepares for war, the authors demonstrate how political and organizational interests determine US defense policy and warn against over-emphasis on planning, centralization, and technocracy. Focusing on the process of defense policy-making rather than just the outcomes of that process, US Defense Politics departs from the traditional style of many textbooks. Designed to help students understand the practical side of American national security policy, the book examines the following key themes:US grand strategy; the roles of the president and the Congress in controlling the military; organizational interests and civil-military relations;who joins America's military; what happens to veterans after wars;how and why weapons are bought;the management of defense and intra- and inter-service relations; public attitudes toward the military;homeland security and the intelligence community.The fourth edition will be essential reading for students of US defense politics, national security policy, and homeland security, and highly recommended for students of US foreign policy, public policy, and public administration
Keywords: Militärpolitik; Sicherheitspolitik; USA